Faktor Penentu Return on Asset pada Bank Umum Syariah: Capital Adequacy Ratio, Operating Expenses Operating Income dan Identitas Etika Islam - Febriani, Elsa Nadiya (Journal Of Islamic Economics And Finance, 2025)
Banking financial institutions are aspects that play an important role in increasing the scale of the economy in Indonesia, one of which is Islamic banking financial institutions. This study aims to analyze the influence of the capital adequacy ratio, operating expenses, operating income, and Islamic ethical identity on financial performance.This study uses a descriptive research type with a quantitative approach. The population of this study is Islamic commercial banks listed on the Indonesian Stock Exchange in 2018-2022. The sample determination used the purposive sampling method and obtained 10 Islamic commercial banks. This study uses descriptive statistical analysis and multiple regression analysis.The results of this study indicate that (1) the Capital Adequacy Ratio does not affect financial performance as proxied by Return On Asset (ROA). ( 2 ) Operating Expenses Operating Income has a significant negative effect on financial performance as proxied by Return on Asset ( ROA ). ( 3 ) Islamic Ethical Identity has a significant negative effect on financial performance as proxied by Return on Asset ( ROA ). ( 4 ) Based on the results of the adjusted R square determination coefficient test of 0.709. This means that the influence of the independent variables, namely the capital adequacy ratio variable, operating expenses operating income, and Islamic ethical identity is 70.9%.